Family role in the achievement of post radical mastectomy self integrity patients - Mekar Dwi Anggraeni (Universiti Kebangsaan Malaysia, 2011)
Breast cancer is the second largest cancer in Indonesia. Patients with advanced-stage breast cancer in particular, are generally filled with anger and depression at the thought of her illness. Family support is essential in patient care, one example is the situation after breast removal surgery (Radical Mastectomy).